The Relationship Between Emotional Intelligence and Student Learning Achievement - Samsidar, Samsidar (PT. Anagata Sembagi Education, 2025)
This study aims to examine the relationship between emotional intelligence and student achievement at the junior high school level. Emotional intelligence includes an individual's ability to recognize, understand, and manage their own emotions and establish interpersonal relationships effectively. In the context of education, emotional intelligence is believed to have a significant influence on learning motivation, stress management, and social interaction in the school environment. This study used a qualitative approach with observation techniques and in-depth interviews with students and teachers in three different schools. The findings showed that students with high levels of emotional intelligence tend to have better learning achievements, characterized by stable academic grades, positive learning attitudes, and the ability to work together with peers. Conversely, students with low emotional intelligence tend to have difficulty in managing conflict, lack focus in learning, and show symptoms of stress that have a negative impact on academic achievement. These findings emphasize the importance of strengthening aspects of emotional intelligence in the learning process in order to create a more holistic learning environment and support students' academic success.